Defected graphene nano-platelets for enhanced hydrophilic nature and visible light-induced photoelectrochemical performances. (May 2017) - Khan, Mohammad Ehtisham; Khan, Mohammad Mansoob; Cho, Moo Hwan
Abstract: This paper reports an optimized electron beam irradiation (60 kGy and 90 kGy) approach for defects-related engineering of graphene nano-platelets for optical and structural properties dependent photoelectrochemical performances. The defects in the electron beam irradiated pristine graphene nano-platelets were studied, analyzed and confirmed using standard characterization techniques such as, diffuse reflectance spectroscopy (DRS), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET), high resolution-transmission electron microscopy (HR-TEM) and contact angle measurements. DRS clearly revealed the increment in the absorption band using electron beam irradiation doses of 60 kGy and 90 kGy. Contact angle measurements confirm the additional hydrophilic nature of the defects engineered graphene nano-platelets in comparison with pristine graphene. The photoelectrochemical performances such as linear sweep voltammetry and electrochemical impedance spectroscopy further confirms the enhancement in the optical, spectroscopic, and photoelectrochemical properties of the 90 kGy defected graphene in comparison to pristine graphene nano-platelets. Therefore, the proposed method is a reliable way of fine-tuning the properties (optical, spectroscopic and photoelectrochemical) of pristine graphene nano-platelets using electron beam irradiation for enhanced photoelectrochemical performance. Graphical abstract: Proposed electron transfer mechanism of defect engineered graphene nano-platelets under visible light irradiation. Highlights: Electron beam irradiated (60 kGy and 90 kGy) pristine graphene. Defects engineered graphene for visible light induced photoelectrochemical performances. Detailed analysis of defects engineered graphene with standard characterization techniques. Defects engineered pristine graphene used as a photoelectrode. Defects engineered graphene as an enhanced hydrophilic in nature.